(untitled) (Tribhuvan University Law Journal, 2025)
All foreign investments come with certain pre-investment expenses, but the legality of such expenses under investment law still largely remains untouched. Can a foreign investor who has invested a significant sum of money in negotiations and followed all legal procedures to obtain a valid permit to proceed with a foreign investment project later be awarded damages under a particular bilateral investment treaty if the government rejects the project citing the government’s actions as a breach of the treaty? Neither Article 25 of the International Centre for Settlement of Investment Disputes (hereafter ICSID) nor the bilateral investment treaties (hereafter BITs) often explicitly address or describe the legal status of this pre-investment expenditure. Clearly defining the legal status of pre-investment expenses is crucial for providing clarity, predictability, and risk mitigation for investors, ensuring their protection. Can those expenses incurred by the foreign investor be interpreted within the meaning of ‘investment’? The first section of the paper seeks to explore the scope of Article 25 of the ICSID Convention, which is significant in deciding the jurisdiction of the ICSID. The definition of an investment, as stated in investment treaties, is discussed in the second section focusing more on first-generation BITs. The third section is devoted to addressing the Mihaly case, which is the first ISDS case that involves determining whether the pre-expenditure cost may be seen as an investment. The fourth section reflects the trends in investor-state arbitration, the new generation BITs that have arisen since the Mihaly case and their implication on both the host state and investor, followed by the overall conclusion.